TEl-IoT: template para elicitar requisitos de sistemas de software IoT - Souza, Sabrina Rocha de (Brasil, 2020)
Industry 4.0 has caused challenges, opportunities and technological concerns for the construction of IoT Software Systems. The characteristics of these systems are related to the capacity of sensing, processing, communication and ubiquity, that is, the “things” that are omnipresent. Thus, the proliferation of intelligent objects has increased in recent years, along with this, the challenges associated with construction, such as document quality, system verification and validation, management of multiple stakeholders, relationship between hardware and software, and functional aspects and non-functional systems. Many methods, techniques and tools have been developed in the area of Requirements Engineering, but little has been explored for this type of system. In this context, the objective of this research is the elaboration of the Template to Elicit Requirements for IoT Software Systems, to support the software engineer during the requirements elicitation activity. The methodology adopted is based on evidence and consists of conducting experimental studies to assess the feasibility of applying the TEl-IoT through its use. The results describe how the TEl-IoT was developed and evaluated based on experimental research methods. In addition, they also present the analysis of the results of the two experimental studies, which indicate the feasibility of their use during requirements elicitation.